White-collar delinquency - Pontell, Henry N. (Crime, law and social change, 2009)
Seemingly harmless pranks by computer hackers have evolved into major economic crimes and acts of terrorism that appear far different than traditional forms of juvenile delinquency. Nonetheless, because they do not occupy the high status positions that facilitate white-collar crimes, serious computer crimes by juveniles have fallen between the theoretical cracks. A new hybrid category of crime that we label "white-collar delinquency" demonstrates that class does matter in the way illegal activity is conceptualized, and re-ignites debates regarding both white-collar crime and juvenile delinquency. We review conceptual issues that relate to this emergent form of computer-based deviance, and identify questions to be addressed in future theorizing and research.